Using a Nowcast approach to assess business cycle conditions in Argentina - D'Amato, Laura Inés (2013)
Real-time judgment of current and future business cycle conditions is one of the mayor challenges monetary policy conduct faces. GDP Nowcasting has been increasingly taken into account by central banks as a measure of immediate perception of economic conditions. We conduct a pseudo-real-time one quarter ahead forecasting exercise of GDP growth using bridge equations. Comparing forecasting performance our results to the typical AR benchmark, we conclude that the Nowcasts is superior in almost 74% of the cases. Using the Giacomoni and White (2004) test, we also concude this dfferences are statistically significant.